Pelatihan penyusunan Ice Breaking untuk penguatan kompetensi calon guru - Asfi Aniuranti; M Happy Nur Tsani; Yasinta Wulandari (Universitas Hamzanwadi, 2021)
In every teaching and learning process includes English teaching, there is a phase called ice breaking. The activity that generally only lasts a few minutes is a paramount aspect. Every English teacher or even the candidate has to be skillful in preparing effective ice breaking. Although ice breaking is viewed as a crucial stage in a teaching process, many students miss this phase when they have to do teaching practice. Therefore, the community service team regarding a workshop about icebreaking is still needed by the students as the teacher candidates. This workshop was conducted online via Google Meet in two days, and the participants were the students of the English Language Teaching Department of Universitas Nahdlatul Ulama Purwokerto. In the workshop, the participants learned the theories related to ice breaking and the examples of ice breaking. They also did some practice on creating ice breaking. Overall, the two-day workshop ran well. The questioner's result also tends to be positive and based on the tasks submitted, the participant's ability to create ice breakers is good enough